2013
DOI: 10.1111/1755-0998.12201
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Nasonia vitripennis outbred laboratory population for genetic analysis

Abstract: The parasitoid wasp genus Nasonia has rapidly become a genetic model system for developmental and evolutionary biology. The release of its genome sequence led to the development of high-resolution genomic tools, for both interspecific and intraspecific research, which has resulted in great advances in understanding Nasonia biology. To further advance the utility of Nasonia vitripennis as a genetic model system and to be able to fully exploit the advantages of its fully sequenced and annotated genome, we develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 80 publications
(140 reference statements)
0
27
0
Order By: Relevance
“…1). Comparable body size differences may also be obtained in other species or lines, such as N. giraulti or the outbred N. vitripennis HVRx line [van de Zande et al, 2014], as shown in online supplementary material S1 (see www.karger.com/doi/10.1159/000480421 for all online suppl. material).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…1). Comparable body size differences may also be obtained in other species or lines, such as N. giraulti or the outbred N. vitripennis HVRx line [van de Zande et al, 2014], as shown in online supplementary material S1 (see www.karger.com/doi/10.1159/000480421 for all online suppl. material).…”
Section: Introductionmentioning
confidence: 88%
“…Genotype does influence the brainbody size relationship to some extent in isogenic T. evanescens lines; however, all those lines exhibited similar (i.e., isometric) brain-body size relations [van der Woude et al, 2013]. A comparison of body length and head width between the AsymCx line and the outbred HVRx line [van de Zande et al, 2014] (outlined in online suppl. material S1) showed that AsymCx is not an "oddball" regarding its size range; equal variation is found in the N. vitripennis outbred line, as well as in a related species, N. giraulti.…”
Section: Groothuis/smidmentioning
confidence: 99%
“…We used a strain of N. vitripennis with relatively high genetic variance (HVRx) as described in Van de Zande et al. (), kept at a constant temperature of 25°C (70% RH, 16/8 L/D). At this temperature N. vitripennis has a generation time of two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…This line was created from wild caught wasps collected from Hoge Veluwe national park in the Netherlands and is maintained as a large outbred population (by mixing stock tubes containing pupae each generation). HVRx was derived from five lines collected in 2001 (van de Zande et al ).…”
Section: Methodsmentioning
confidence: 99%
“…After seven days the hosts were removed from the tubes, mixed with the hosts from all other replicates of the same strain, and redistributed into six fresh tubes (to maintain an outbred population). The parasitized hosts were kept in an incubator at 25°C, and the next generation emerged after 2 weeks and were re‐hosted again 48 h later (see van de Zande et al for further details regarding the initiation of HVRx).…”
Section: Methodsmentioning
confidence: 99%